Implementation and outcome evaluation of the Medical Education Partnership Initiative biostatistical reasoning workshops for faculty and postgraduate students at the University of KwaZuluNatal Durban South Africa - Glenda Matthews; Moise Muzigaba; Mary Thompson; Benn Sartorius; Nisha Nadesan-Reddy; Sandy Pillay; Lalloo Umesh (South African Medical Association, 2016)
Background. There is a shortage of biostatistics expertise at the University of KwaZulu-Natal (UKZN), Durban, South Africa and in the African region.This constrains the ability to carry out high-quality health research in the region. Objectives. To quantitatively and qualitatively evaluate a programme designed to improve the conceptual and critical understanding of biostatistical concepts of UKZN health researchers. Methods. A 40-hour workshop in biostatistical reasoning was conducted annually between 2012 and 2015. The workshops were structured around interpretation and critical assessment of nine articles from the medical literature, with a mix of in-class sessions and small group discussions. Quantitative evaluation of the knowledge gained from the workshops was carried out using a pre- and post-workshop quiz, and qualitative evaluation of the workshop process was done using a mid-workshop questionnaire and focus group discussions. Results. For each year that the workshop was conducted, post-workshop quiz scores were significantly higher than pre-workshop scores. When quiz assessments from all 4 years of training were combined, the pretest median score was 55% (interquartile range (IQR) 40 - 62%) and the post-test median score was 68% (IQR 62 - 76%), with p<0.0001 for the overall comparison of pre- v. post-scores. There was a general consensus among participants that the workshop improved their reasoning skills in biostatistics. Participants also recognised the value of the workshop in building biostatical capacity at UKZN. Conclusion. The workshops were well received and improved the critical and conceptual understanding of the participants. This education mode offers the opportunity for health researchers to advance their knowledge in settings where there are few professional biostatistician collaborators.